Estudo teórico das propriedades eletrônicas e ópticas de nanoestruras BxNyCz - Leite, Lázaro Genilson da Silva (2019)
Graphene, a two-dimensional lattice of carbon atoms, has been widely studied during the past few years. One of the great interest in this material is due to its possible technological applications. The opening of a energy gap in graphene is probably one of the most important and urgent topics in its research currently, since most of the proposed applications for graphene in nanoelectronic devices require the ability to adjust its gap. Thehexagonalboronnitride(h-BN) is a structurally similar material to graphene and has some physical and chemical properties considered unique. However, the adjustment of some of its properties is also indispensable so that they can be used as basic components in nanoelectronics and spintronics. All these systems have widely tunable properties and there are several theoretical and experimental methods which can be used for this purpose, one of them is h-BN doped graphene. This was recently synthesized and proved to be an efﬁcient method to open the gap in graphene, obtaining hybrid nanomaterials with intermediate properties between grapheneandh-BN.The control of the size of the doping domain allows us to adapt the electronic structure and other properties. In this context, using ﬁrst-principles calculations, based on the density functional theory (DFT), we investigated the changes caused in the electronic, magnetic and optical properties due to the doping of graphene with h-BN and also study the chemical adsorption of hydrogen in these hybrid nanoestructures. As a consequence of the study of these hybrid nanostructures, we observed a number of new results in the properties electronic, magnetic and optical.